(untitled) (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2025)
Shooting proficiency is a crucial competency required of Indonesian Air Force soldiers, relying not only on physical technique but also on mental preparedness in high-pressure situations. However, results from long-barreled weapon shooting training at Sjamsudin Noor Air Force Base indicate that a majority of personnel have not achieved optimal accuracy levels. This study aims to enhance shooting accuracy through the implementation of visualization and imagery-based mental training techniques. Adopting the Kemmis and McTaggart Sports Action Research (PTO) model, the study was conducted in two cycles with ten Indonesian Air Force members selected purposively as subjects. The assessment instruments included a shooting accuracy test (10 shots in a prone position) and a mental readiness questionnaire utilizing a Likert scale. Findings revealed an increase in average accuracy scores from 38.30 in the pre-action phase to 52.60 in Cycle I, and further to 64.60 in Cycle II. Additionally, the mental readiness questionnaire scores improved, ranging from 4.0 to 4.3, indicating a significant enhancement in participants’ concentration, calmness, and self-confidence. In conclusion, the use of imagery has proven to be effective in boosting both technical skills and psychological readiness in shooting training. This approach can be systematically integrated into military training programs to strengthen individual performance under stress.